Effect of Economic Growth on Poverty in Bima City - Anggun Aisatun Zahroh; Puji Muniarty; Julaiha Julaiha (Ilomata International Journal of Management, 2020)
Natural disasters and inflation that occurred in the city of Bima caused economic growth to slow down and cause the impact of social inequality that causes poverty. This study aims to analyze the effect of independent variables on the dependent variable. The independent variable in this study is economic growth while the dependent variable is poverty in the City of Bima for the period 2012-2018. The sample in this study is economic growth in the form of GDRP data based on constant prices and poverty over the past 7 years, from 2012 to 2018. The data used in this study are in the form of a list of tables on economic growth in the form of GDRP based on constant prices and poverty during 7 years obtained from the Central Statistics Agency office in Bima City. The data used are secondary data and the method used is simple linear regression analysis, simple correlation coefficient, simple linear determination and t test (2 parties) using SPSS Version 21.0 to obtain a comprehensive picture of the relationship between one variable with another variable. The results showed that economic growth had no effect and was not significant on poverty in the Bima city.